IMPLEMENTASI MODEL PICTURE AND PICTURE BERBANTUAN GENIALLY DAN PENILAIAN DIGITAL UNTUK MENINGKATKAN PEMAHAMAN MATERI PELESTARIAN LINGKUNGAN - Gisela Anantasia; Sulastri Rini Rindrayani (CV. Adiba Aisha Amira, 2025)
This article discusses an educational innovation in Social Studies (IPS) through the implementation of the Picture and Picture model supported by interactive media Genially and digital assessment using Microsoft Forms. This study is based on a literature review from various relevant sources and aims to develop an innovative learning design aligned with the principles of the Merdeka Curriculum. The findings indicate that the combination of visual models and interactive digital media can enhance students' understanding of environmental conservation materials, increase active participation, and support more effective and efficient assessment.